ByzRev 05.2023.003: Reinhart Ceulemans – Barbara Crostini (eds), Receptions of the Bible in Byzantium: Texts, Manuscripts, and their Readers.: Texts, Manuscripts, and their Readers (Acta Universitatis Upsaliensis. Studia Byzantina Upsaliensia 20). Uppsala: Uppsala Universitet 2021. - Albrecht, Felix (The Byzantine Review, 2023)
Reinhart Ceulemans – Barbara Crostini(eds), Receptions of the Bible in Byzantium. Texts, Manuscripts, and their Readers (Acta Universitatis Upsaliensis. Studia Byzantina Upsaliensia 20). Uppsala: Uppsala Universitet 2021. XX, 534 pp. – ISBN: 978-91-513-1017-6.